The Reality of Strategic Human Capital Development in Small and Medium Enterprises. - Mahapa, Mildred; Chirasha, Vonai (Advances in Social Sciences Research Journal, 2017)
Human capital is vital for any organization for the attainment of organizational objectives. Developing the human capital thus becomes a critical conduit to the attainment of organizational objective. There has been an increase in the number of Small and Medium Enterprises (SMEs) in Zimbabwe and human resource management has become very critical. The human resource is the only resource that can provide competitive advantage amongst rivals. This paper seeks to highlight the challenges faced by small and medium enterprises in effectively implementing human capital development (HCD). Qualitative research methodology was used as the main research approach in the study. Two small and two medium mining organisations were conveniently identified in Gweru and used as case studies. Data was gathered mainly through the use of face to face interviews with 12 participants. It was obtained that both small and medium enterprises view human capital development as very important in their operations. However they pointed out that they cannot employ HCD effectively as they have limited financial resources, lack of skilled staff, lack of expert knowledge on human resource issues as well as lack of effective employee retention strategies. The researcher recommends that the small and medium enterprises forms partnerships with other organisations so as to mobilise resource and also for knowledge sharing.